2014
DOI: 10.4103/2141-9248.141550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of missed first appointments among outpatients at a Psychiatric Hospital in Nigeria

Abstract: Background:Missed appointments are common in psychiatric practice. It compromises quality of care, results in poor treatment outcomes and drains financial resources. In Nigeria, where mental health services are poorly organized, missed appointments and its resultant consequences may be burdensome.Aim:This study sought to determine the prevalence and factors (sociodemographic and clinical) associated with missed clinic appointments at a regional psychiatric hospital.Subjects and Methods:A study on a cohort of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The prevalence of missed first out-patient clinic appointments obtained in this study is similar to that found by a previous study in the same setting, 24 although the study population in the latter consisted of patients with different psychiatric disorders. It is also consistent with the range of values obtained in other studies on out-patient default (17–46%).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of missed first out-patient clinic appointments obtained in this study is similar to that found by a previous study in the same setting, 24 although the study population in the latter consisted of patients with different psychiatric disorders. It is also consistent with the range of values obtained in other studies on out-patient default (17–46%).…”
Section: Discussionsupporting
confidence: 88%
“…Time spent with care providers was considered too short by patients. Other studies have reported long waiting time caused by delays in moving from one service point to another, attitudes of staff, and low staff-patient ratio [40, 41]. May be, low staff-patient ratio could explain the delay in seeing patients as a result of increasing number of patients as discussed in the following paragraph.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of missed appointments, data from general adult clinics suggest that the rates range from 14% to 64%. [ 4 6 7 8 ] The dropout rates reported across various studies also suggest that about 31%–64% of patients do not come back for their first outpatient appointments after hospitalization, with an average nonattendance rate being 50% for the initial appointments. [ 6 7 9 10 ]…”
Section: Introductionmentioning
confidence: 99%